Internações hospitalares e mortalidade por fratura de fêmur em idosos na rede pública de saúde do Brasil entre 1992-2008: modelos de previsão, sazonalidade e relação com variáveis meteorológicas - Castro, Alessandra Paiva de (2011)
Introduction. There is a lack of information on epidemiological trends and seasonal variation relating to femoral fractures among elderly people in Brazil. This study had the aims of examining the historical series of hospital admissions and intrahospital mortality due to femoral fractures among elderly Brazilians, within the public healthcare system; ascertaining whether any trend or periodicity exists (and the correlation with climatic variables); making predictions; and verifying differences between brazilian regions, genders and age groups. Method. Monthly data from the hospital information system of the national healthcare system relating to hospitalizations and mortality due to femoral fractures among elderly people, covering 1992-2008, were used. Population-based coefficients of hospital admission were calculated from the resident populations, according to sex and age group in each region of Brazil, and were analyzed using time series analysis methods, to ascertain seasonal variations and adjust predictive models. Then, monthly meteorological data (compensated mean temperature, maximum temperature, minimum temperature, mean relative air humidity, total insolation, number of days with precipitation and total accumulated rainfall) relating to the period from 1992 to 2009 were used, from Porto Alegre, Curitiba, São Paulo, Belo Horizonte, Rio de Janeiro, Goiânia, Salvador, Fortaleza, Teresina and Manaus. The numbers of hospital admissions due to femoral fractures within the public healthcare system in ten Brazilian state capitals during the study period were gathered from the DATASUS database. Results. The southeastern region presented the highest mean coefficients, followed by the central-western and southern regions. Older age groups and females presented higher coefficients of hospitalization. There was a seasonal pattern, with higher coefficients in the winter for all age groups, both sexes and all regions except northern Brazil. From 1992 to 2008, a significant reduction in coefficients occurred (24.4%), but the time series revealed an increasing trend starting in 2001, which presented a projected increase in the coefficient of hospitalization for Brazil of 27% by 2018. However, among elderly individuals over the age of 80 and in the central-western region, decreases in the coefficient were projected. The mortality rate was 4.1% over the study period. The southeastern region, older age groups and males presented higher mortality rates. The time series for Brazil, females, the age group from 70 to 79 years, the northern region and the southeastern region presented semestral periodicity, with higher mortality rates in the winter and summer and lower rates in the spring and autumn. Between 1992 and 2008, there was no significant variation in the rate, but by 2018, there will be an increase of around 45%. Seasonality was observed in the femoral fracture coefficients in the seven state capitals of higher latitude, while it was not observed in the three capitals of lower latitude. The climatic factor that presented the greatest correlation with the fracture coefficients was the minimum temperature (r = -0.5 in São Paulo). In most of the state capitals, the correlation was inverse and delayed by one month. In some state capitals, there was also a negative correlation with precipitation, with delays that ranged from one to three months. The correlations with humidity and insolation were less consistent and of lower intensity. Conclusions. Many issues in epidemiology of femoral fractures in Brazilian older people were clarified.